Dialogues and debates from late antiquity to late Byzantium
1 online resource (x, 283 pages)
Keywords: "Dialogues and Debates from Late Antiquity to Late Byzantium offers the first overall discussion of the literary and philosophical dialogue tradition in Greek from imperial Rome to the end of the Byzantine empire and beyond. Sixteen case studies combine theoretical approaches with in-depth analysis and include comparisons with the neighbouring Syriac, Georgian, Armenian, and Latin traditions. Following an introduction and a discussion of Plutarch as a writer of dialogues, other chapters consider the Erostrophus, a philosophical dialogue in Syriac, John Chrysostom's On Priesthood, issues of literariness and complexity in the Greek Adversus Iudaeos dialogues, the Trophies of Damascus, Maximus Confessor's Liber asceticus, and the middle Byzantine apocryphal revelation dialogues. The volume demonstrates a new frequency in middle and late Byzantium of rhetorical, theological and literary dialogues, concomitant with the increasing rhetoricisation of Byzantine literature, and argues for a move towards new and exciting experiments"--Provided by publisher.